People and landscapes of the chilean Pacific ocean and southern Perú, seen by a british corsair: Account of the journey of Thomas Cavendish from the western access of the strait of Magellan to the bay of Aricain 1587 - Silva Galdames, Osvaldo; Téllez Lúgaro, Eduardo (Cuadernos de Historia, 2019)
We publish part of the story left by Francis Pretty, chronicler of the privateer expedition headed by Thomas Cavendish, relating to incidents and impressions that English sailors over the course of its course formed along the coast of the Kingdom of Chile and the coast of southernmost ofthe Viceroyalty of Peru, between January and may of 1587, in the context of the voyage of circumnavigation executed by Cavendish across the globe (1586-88). Its translation to the Spanish has been based on the version of the text composed by Pretty edited in Hakluyt’s collection (vol. IV, 1811).